2020
DOI: 10.1088/1361-6528/ab8669
|View full text |Cite
|
Sign up to set email alerts
|

Ti3C2 (MXene) based field electron emitters

Abstract: As a novel class of two-dimensional materials, MXene has provoked tremendous progress for various applications in functional devices. Here, we pioneer a preliminary understanding on the field emission behavior of MXene for the first time. Ti3C2 paper is fabricated by using facile filtration method, and multiple vertical sheets appear on the surface of MXene paper with high electrical conductivity (2.93 × 105 S m−1) and low work function (3.77 eV). The field electron emission performance and electric field dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…In this context, Chen et al first examined the FE behavior of Ti 3 C 2 MXene paper and obtained a turn-on field of 7.6 V μm −1 at a current density of 0.1 mA cm −2 . 37 Following this, an improvement in the FE characteristics of a Ti 3 C 2 T X MXene via plasma treatment has been reported by Hong et al 38 It has been observed that the H 2 -plasma-treated MXene thin film emitter displayed a turn-on field of 8.5 V μm −1 . Wu et al reported excellent field emission properties of the MXene that was fabricated by etching of the Al layer from Ti 3 AlC 2 .…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In this context, Chen et al first examined the FE behavior of Ti 3 C 2 MXene paper and obtained a turn-on field of 7.6 V μm −1 at a current density of 0.1 mA cm −2 . 37 Following this, an improvement in the FE characteristics of a Ti 3 C 2 T X MXene via plasma treatment has been reported by Hong et al 38 It has been observed that the H 2 -plasma-treated MXene thin film emitter displayed a turn-on field of 8.5 V μm −1 . Wu et al reported excellent field emission properties of the MXene that was fabricated by etching of the Al layer from Ti 3 AlC 2 .…”
Section: Introductionmentioning
confidence: 73%
“…In addition to the aforementioned applications, like the layered 2-D materials, MXenes have attracted the attention of field emission researchers. In this context, Chen et al first examined the FE behavior of Ti 3 C 2 MXene paper and obtained a turn-on field of 7.6 V μm –1 at a current density of 0.1 mA cm –2 . Following this, an improvement in the FE characteristics of a Ti 3 C 2 T X MXene via plasma treatment has been reported by Hong et al It has been observed that the H 2 -plasma-treated MXene thin film emitter displayed a turn-on field of 8.5 V μm –1 .…”
Section: Introductionmentioning
confidence: 98%
“…Although Ti 3 C 2 T x with good conductivity in some electronic devices is widely studied in research, such as supercapacitors, [ 22 ] metal ion batteries, [ 104 ] sensors, [ 25 ] and so on. Nevertheless, only a small amount of work reports the application of Ti 3 C 2 T x MXene on vacuum electronic devices or semiconductor electronic devices such as field emission devices, [ 14c,27 ] transistors, [ 107a ] triboelectric nanogenerators (TENG), [ 90,109 ] and so on, all of which still requires lots of research efforts to implement them.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, MXene is widely used in capacitive de‐ionization, [ 19 ] electromagnetic interference, [ 20 ] metal ion batteries, [ 21 ] supercapacitors, [ 22 ] transparent conductors, [ 23 ] electrocatalysis and photocatalysis, [ 24 ] gas sensors and biosensors, [ 25 ] thermoelectric materials, [ 26 ] and many other aspects. [ 27 ] Prospectively, MXene has extraordinary electronic applications because of its excellent electrical conductivity. Therefore, improving the electrical conductivity of MXene has become a major difficulty in current researches, and thus a research hotspot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation